Development and Evaluation of PolyherbalTopical Cream for Wound Healing Applications Using Alum, Turmeric, and Aloe Vera - Amar M. Raval,; Rathod Jainish Maneklal,; Makwana Utsav Dilipbhai, (Asian Journal of Pharmaceutical Research and Development, 2026)
Background: Hypertension (HTN) remained a major global health concern and a leading risk factor for cardiovascular morbidity Wound healing is a complex biological process involving hemostasis, inflammation, proliferation, and tissue remodeling. Herbal formulations have gained significant interest due to their safety, effectiveness, and reduced adverse effects compared to synthetic products. The present study aimed to formulate and evaluate a polyherbal wound healing cream containing alum, turmeric, and aloe vera using an oil-in-water emulsion base. Different batches (F1, F2, and F3) were prepared by varying the concentration of excipients such as stearic acid, cetyl alcohol, glycerin, and herbal extracts. The prepared formulations were evaluated for appearance, pH, spreadability, homogeneity, greasiness, phase separation, washability, skin irritation, and stability. The results indicated that all formulations showed acceptable physical characteristics. Batch F3 demonstrated superior properties with good spreadability, light yellow appearance, pleasant odor, no phase separation, and excellent stability. The study concluded that the developed polyherbal cream possesses promising potential for wound care applications.